2016
DOI: 10.1163/22941932-20160118
|View full text |Cite
|
Sign up to set email alerts
|

Timing of vessel formation in twigs and trunks in relation to porosity and leaf flushing

Abstract: In order to understand the coordination of leaf phenology and functional xylem anatomy, the timing of vessel wall lignification in twigs and stems in relation to leaf appearance was studied in nine species with different porosity patterns. Cylindrical stem cores and twigs were collected from early spring through late summer from deciduous (Quercus serrata, Liquidambar styraciflua, and Acanthopanax sciadophylloides), and evergreen (Castanopsis cuspidata; Cinnamomum camphora, Ilex pedunculosa, Symplocos prunifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…Twig vessel elements began to lignify prior to bud opening [14], and cell division at the bud bases began before or at the same time as bud break in both ring-and diffuse-porous trees [10]. Previous studies have shown that lignification of almost all of the first-formed vessels occurs within ±2 weeks of leaf appearance [7], e.g., 0 week and 0-3 weeks before leaf appearance in ring-porous Quercus serrata and diffuse-porous Liquidambar styraciflua, respectively [25]. In the present study, almost all of the first-formed vessels in twigs lignified during the period when leaf area was between 0% and 70% of the maximum, not only in deciduous species but also in evergreen species (Figures 1 and 2A), though evergreen species have perennial leaves.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Twig vessel elements began to lignify prior to bud opening [14], and cell division at the bud bases began before or at the same time as bud break in both ring-and diffuse-porous trees [10]. Previous studies have shown that lignification of almost all of the first-formed vessels occurs within ±2 weeks of leaf appearance [7], e.g., 0 week and 0-3 weeks before leaf appearance in ring-porous Quercus serrata and diffuse-porous Liquidambar styraciflua, respectively [25]. In the present study, almost all of the first-formed vessels in twigs lignified during the period when leaf area was between 0% and 70% of the maximum, not only in deciduous species but also in evergreen species (Figures 1 and 2A), though evergreen species have perennial leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are similar to these previous findings. Lignification of the first-formed trunk vessels occurred until full leaf expansion (71-84%LA) in ring-porous Q. serrata and after full leaf expansion in diffuse-porous L. styraciflua ( Figures 1A and 2B), i.e., 2-4 weeks before and more than 7 weeks after leaf appearance, respectively [25]. Previous studies have reported that the wide vessels of the inner ring in ring-porous species are not used for water transport [23,[36][37][38][39], and sap flow increases with the increase in leaf area index (LAI) [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations